2010
DOI: 10.1021/cm1000472
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of the Cr(III)−Fe(III) (Oxy)hydroxide Compositional Series: Insights for a Nanomaterial “Solid Solution”

Abstract: Chromium(III) (oxy)hydroxide and mixed Cr(III)−Fe(III) (oxy)hydroxides are environmentally important compounds for controlling chromium speciation and bioaccessibility in soils and aquatic systems and are also industrially important as precursors for materials and catalyst synthesis. However, direct characterization of the atomic arrangements of these materials is complicated because of their amorphous X-ray properties. This study involves synthesis of the complete Cr(III)−Fe(III) (oxy)hydroxide compositional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 55 publications
(109 reference statements)
10
73
2
Order By: Relevance
“…When compared with the pattern of pure goethite, a displacement of the total broadband toward smaller 2θ values was observed in the pattern of Cr-goethites with increasing Cr(III) content, and the unit cell parameters (a, b, c) of Cr-goethite decreased from 4.614 to 4.608 Å, 9.965 to 9.942 Å, and 3.024 to 3.019 Å, respectively (Table 1). These results revealed that Cr(III) was incorporated in the goethite structure, which resulted in the change of unit cell parameters [35,36]. The SEM results were consistent with the XRD analyses, showing that the crystalline morphology of 9.03% Cr-goethite was generally needlelike, but more broken than that of pure goethite (Figure 2).…”
Section: Properties Of Cr-goethitesupporting
confidence: 74%
“…When compared with the pattern of pure goethite, a displacement of the total broadband toward smaller 2θ values was observed in the pattern of Cr-goethites with increasing Cr(III) content, and the unit cell parameters (a, b, c) of Cr-goethite decreased from 4.614 to 4.608 Å, 9.965 to 9.942 Å, and 3.024 to 3.019 Å, respectively (Table 1). These results revealed that Cr(III) was incorporated in the goethite structure, which resulted in the change of unit cell parameters [35,36]. The SEM results were consistent with the XRD analyses, showing that the crystalline morphology of 9.03% Cr-goethite was generally needlelike, but more broken than that of pure goethite (Figure 2).…”
Section: Properties Of Cr-goethitesupporting
confidence: 74%
“…On the other hand, as water in the Cr(OH) 3 structure is involved in the HER, water has to be replaced by water molecules from the solution, otherwise the film will be destroyed. However, this is hampered by the slow ligand exchange of Cr(OH) 3 as described by Tang et al [49] and Rustad and Casey [50]. This is corroborated by the results presented by Larses et al [48], who showed increased overpotentials for the HER with increasing Cr content in the Fe 1-x Cr x OOH structure.…”
Section: Reaction Kineticsmentioning
confidence: 56%
“…This does not preclude heterogeneity on larger length scales, but without crystallographic coherence, which may affect energetics and decomposition behavior. A previous study of nanocrystalline Fe,Cr oxyhydroxides (Tang et al, 2010), showed the evolution of domain size and structure with composition, which may be an analog for the behavior of the ACC-AMC system. Theoretical studies have also pointed to the possibility that the ACC structure is composed of hydrated clusters whose size dependent thermodynamic stability increases concomitantly with their water content (Raiteri and gale, 2010).…”
Section: Structure and Energetics Of Amorphous Solid Solutionsmentioning
confidence: 80%